2011
DOI: 10.1073/pnas.1103746108
|View full text |Cite
|
Sign up to set email alerts
|

The mammalian target of rapamycin regulates cholesterol biosynthetic gene expression and exhibits a rapamycin-resistant transcriptional profile

Abstract: The mammalian target of rapamycin (mTOR) is a central regulator of cell growth and proliferation in response to growth factor and nutrient signaling. Consequently, this kinase is implicated in metabolic diseases including cancer and diabetes, so there is great interest in understanding the complete spectrum of mTOR-regulated networks. mTOR exists in two functionally distinct complexes, mTORC1 and mTORC2, and whereas the natural product rapamycin inhibits only a subset of mTORC1 functions, recently developed AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 40 publications
5
82
0
Order By: Relevance
“…The transcription level of SQLE, LSS, and HMGCR was not altered upon the elevation of plasmalogens (Fig. 4B), where the transcription level of these enzymes was lowered with rapamycin (24). Furthermore, cycloheximide chase experiments using HeLa cells in the presence of Etn revealed that elevation of plasmalogens stimulated degradation of SQLE as compared with the turnover of SQLE in the absence of Etn (Fig.…”
Section: Elevation Of Plasmalogens Causes Degradation Of Sqle In a Mamentioning
confidence: 83%
See 1 more Smart Citation
“…The transcription level of SQLE, LSS, and HMGCR was not altered upon the elevation of plasmalogens (Fig. 4B), where the transcription level of these enzymes was lowered with rapamycin (24). Furthermore, cycloheximide chase experiments using HeLa cells in the presence of Etn revealed that elevation of plasmalogens stimulated degradation of SQLE as compared with the turnover of SQLE in the absence of Etn (Fig.…”
Section: Elevation Of Plasmalogens Causes Degradation Of Sqle In a Mamentioning
confidence: 83%
“…Primers for Chinese hamster SQLE (12) and LSS (25), and human LSS and HMGCR (24) were listed in supplemental Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…Transgenic mice with cardiomyocyte-restricted expression of human mutant nebulette develop dilated cardiomyopathy at 6 months of age (48). Although rapamycin is a mTORC1 inhibitor, it potently inhibits only the phosphorylation of S6K, but not 4E-BP1 and cap-dependent translation, in mammalian cells (35,36,49). Therefore, rapamycin may not completely inhibit protein synthesis in the mammalian system.…”
Section: D-dige Spotmentioning
confidence: 99%
“…Using an in vitro kinase assay, we found that vPK phosphorylates S6 peptide at the same residues phosphorylated by S6KB1 (S235, S236), which denotes activation of protein translation. Moreover, DG2, a S6KB1-specific kinase inhibitor (21,22), abolished phosphotransferase activity of both S6KB1 and vPK, underscoring the similarity of the active sites of these two kinases. Through ectopic vPK expression in both epithelial (293) and endothelial (HUVEC) cells, we confirmed that vPK phosphorylates S6, the furthest downstream effector of PI3K/AKT/mTOR signaling.…”
Section: Discussionmentioning
confidence: 88%
“…2A). Addition of DG2, a selective S6KB1 inhibitor, ablated phosphotransferase activity of both S6KB1 and vPK (21,22). DG2 was designed to selectively bind the active site of S6KB1; thus, the ability of DG2 to inhibit vPK to levels similar to S6KB1 confirmed the similarity in active sites of these kinases (Fig.…”
Section: Significancementioning
confidence: 81%